2022
DOI: 10.21744/ijhms.v5n1.1851
|View full text |Cite
|
Sign up to set email alerts
|

Current update on stroke ischemic management

Abstract: Stroke is one of the most important causes of morbidity and mortality worldwide, with survivors subjected to long-term disability. Stroke is classified as ischemic and hemorrhagic. 87 % of strokes are classified as ischemic. Except for thrombolytic therapy, there is no established treatment to reduce the neurological deficits caused by an ischemic stroke. Therefore, it is necessary to develop new therapeutic strategies designed to improve neurological functions after ischemic stroke. Stem cell-based therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In our study the total amount of a components in the GCF and interactions between the GCF components and periodontal diseases were observed. [3,7,8]. We observed that the total RANKL levels in GCF were higher in the both of periodontitis group than CTRL group and this levels were decreased after NSPT and the total amount of OPG were statistically lower in the both of periodontitis groups than CTRL group at baseline.…”
Section: Discussionmentioning
confidence: 62%
“…In our study the total amount of a components in the GCF and interactions between the GCF components and periodontal diseases were observed. [3,7,8]. We observed that the total RANKL levels in GCF were higher in the both of periodontitis group than CTRL group and this levels were decreased after NSPT and the total amount of OPG were statistically lower in the both of periodontitis groups than CTRL group at baseline.…”
Section: Discussionmentioning
confidence: 62%
“…I don't know if the medicine is taken or not." This expression shows that there is a possibility of noncompliance in the treatment carried out by NN's parents so that the disease is transmitted to her (Rodnyansky et al, 2021;Permana et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Ali et al(2009) [9] , hypertension was found in 75 percent of patients, followed by smoking (51 percent) and diabetes (49 percent ). According to Naik et al (2006) [10] , smoking is the most common risk factor (40.66 percent), followed by hypertension (40 percent ) Red Cell Distribution Width The study found that 0.00 [11]discovered that mean RDW was significantly higher in people with stroke than in people without stroke (13.7 percent vs 13.2 percent, p0.001). This was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%